Rapid Measurement of Urinary Trypsinogen-2 as a Screening Test for Acute Pancreatitis - Esko Kemppainen; Johan Hedström; Pauli Puolakkainen; V Sainio; Reijo Haapiainen; Vesa Perhoniemi; Sirpa Osman; E. Kivilaakso; Ulf-Håkan Stenman (1997)
Acute pancreatitis can be difficult to diagnose. We developed a rapid dipstick screening test for pancreatitis, based on the immunochromatographic measurement of urinary trypsinogen-2.We prospectively compared the urinary trypsinogen-2 dipstick test with a quantitative urinary trypsinogen-2 assay, a urinary dipstick test for amylase, and serum and urinary amylase assays in 500 consecutive patients with acute abdominal pain at two emergency departments. Acute pancreatitis was diagnosed according to standardized criteria.The urinary trypsinogen-2 dipstick test was positive in 50 of the 53 patients with acute pancreatitis (sensitivity, 94 percent), including all 7 with severe pancreatitis. Two patients with urinary trypsinogen-2 concentrations below the sensitivity threshold of the test (50 ng per milliliter) and one with a very high concentration had false negative results. The test was also positive in 21 of the 447 patients without pancreatitis (specificity, 95 percent), including 7 with abdominal cancers, 3 with cholangitis, and 2 with chronic pancreatitis. The sensitivity and specificity of the dipstick test were similar to those of the quantitative urinary trypsinogen-2 assay and higher than those of the urinary amylase dipstick test. The serum amylase assay had a sensitivity of 85 percent (with a cutoff value of 300 U per liter for the upper reference limit) and a specificity of 91 percent. The sensitivity and specificity of the urinary amylase assay (cutoff value, 2000 U per liter) were 83 and 88 percent, respectively.In patients with acute abdominal pain seen in the emergency department, a negative dipstick test for urinary trypsinogen-2 rules out acute pancreatitis with a high degree of probability. A positive test usually identifies patients in need of further evaluation.